THE POLICING MODEL IN MANAGING THE YOUTH ORGANIZATION CONFLICT IN MEDAN, INDONESIA: CASE STUDY OF IKATAN PEMUDA KARYA (IPK) AND PEMUDA PANCASILA (PP) CONFLICT - Saragih, Benny Maringan (International Review of Humanities Studies, 2019)
Medan has multicultural and composite area. Medan is the capital city of Indonesia Province of North Sumatra, Indonesia. Medan is the largets city in Sumatra island. There are 13 ethnic groups in Medan. The heterogeneity of people in Medan has bring out several youth organizations with their slogans and ideologies. The youth organizations is also one of freedom and rights for every citizen that guaranteed and protected by the state. The youth organization is increasingly synonymous with thuggery and crime action. this research focuses on resolving PP and IPK‟s conflict influenced by three main factors: resource aquisition and economics motive, existence and dominations, and past incident. This research is qualitative research using the theory of community policing that has developed. The result of this research is the importance of multidisciplinary community policing to resolve conflict. The police must cooperate with government institutions, members and community groups, non-profit organizations, service providers, and private businesses. The presence of government institutions, service providers and private businesses, will reduce member dependence on jobs provided by Youth Organization, and the presence of community groups will assist the police in reducing and preventing conflicts between youth organization, but the police must also facilitate the public in terms of reporting and others, such as by utilizing IT.